Incentive-Enhancing Preferences: Personality, Behavior, and Earnings - Bowles, Samuel; Gintis, Herbert; Osborne, Melissa (American Economic Review, 2001)
Incentive-Enhancing Preferences: Personality, Behavior, and Earnings by Samuel Bowles, Herbert Gintis and Melissa Osborne. Published in volume 91, issue 2, pages 155-158 of American Economic Review, May 2001